2013
DOI: 10.1186/2193-1801-2-405
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fungal flora in raw milk from the Italian Alps in relation to pasture altitude

Abstract: The present paper explores the diversity of mycobiota inhabiting raw milk sampled at different altitudes (1400 m, 1800 m, 2200 m) from cows grazing Alpine pastures of Valle d’Aosta (North-Western Italian Alps). To this aim, multilocus sequencing was performed at barcodes commonly used for fungal identification (ITS1, D1/D2 domains of the 26S rRNA gene, and part of the β-tubulin gene). A total of 31 species were detected, most of them yeasts, followed by moulds and by 2 sequences of macroscopic fungi. Several y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
11
0
5
Order By: Relevance
“…This is especially true for yeasts and moulds, whose occurrence and diversity in vegetable coagulants have been very poorly explored (Roseiro et al ., ). The importance of these microorganisms in cheese manufacturing is being increasingly acknowledged, due to the many beneficial activities of these microorganisms, including the excretion of growth factors (especially vitamins), the metabolization of lactate/lactose, which enhances the growth of a secondary microbiota constituted by acid‐sensitive bacteria, the production of alkaline metabolites and aromatic compounds, the inhibition of spoilage microorganisms, the enhancement of cheese flavour and aroma through proteolysis and lipolysis, and even probiosis (Beresford et al ., ; Jacques and Casaregola, ; Panelli et al ., ; Padilla et al ., ; Cardoso et al ., ). On the other hand, fungi can also act as spoilage microorganisms, causing cheese defects such as cheese softening, superficial discoloration, early blowing and the development of off‐flavours (Fleet, ; Jakobsen and Narvhus, ; Carreira et al ., ; Wyder et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…This is especially true for yeasts and moulds, whose occurrence and diversity in vegetable coagulants have been very poorly explored (Roseiro et al ., ). The importance of these microorganisms in cheese manufacturing is being increasingly acknowledged, due to the many beneficial activities of these microorganisms, including the excretion of growth factors (especially vitamins), the metabolization of lactate/lactose, which enhances the growth of a secondary microbiota constituted by acid‐sensitive bacteria, the production of alkaline metabolites and aromatic compounds, the inhibition of spoilage microorganisms, the enhancement of cheese flavour and aroma through proteolysis and lipolysis, and even probiosis (Beresford et al ., ; Jacques and Casaregola, ; Panelli et al ., ; Padilla et al ., ; Cardoso et al ., ). On the other hand, fungi can also act as spoilage microorganisms, causing cheese defects such as cheese softening, superficial discoloration, early blowing and the development of off‐flavours (Fleet, ; Jakobsen and Narvhus, ; Carreira et al ., ; Wyder et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Most authors suggest, however, that fungi found in raw milk are typically heat sensitive and that raw milk is thus not an important (direct) source of fungi found in dairy products (Jacques and Casaregola, 2008). A few studies have surveyed the diversity of fungi in raw milk and reported that yeasts are more frequently isolated from raw milk than molds (Callon et al, 2007;Delavenne et al, 2011;Panelli et al, 2013). For example, Panelli et al (2013) tested 40 bulk milk samples across the Italian Alps and most frequently isolated Kluyveromyces marxianus, Atrotorquata lineata, and Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have surveyed the diversity of fungi in raw milk and reported that yeasts are more frequently isolated from raw milk than molds (Callon et al, 2007;Delavenne et al, 2011;Panelli et al, 2013). For example, Panelli et al (2013) tested 40 bulk milk samples across the Italian Alps and most frequently isolated Kluyveromyces marxianus, Atrotorquata lineata, and Candida spp. Importantly, these studies identified some fungal species that had not previously been found in raw milk, suggesting that the fungal diversity associated with raw milk remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…They are longitudinally striate and have 5 to 7 germ slits at each apex. Kohlmeyer and Volkmann-Kohlmeyer further suggest that A. lineata is probably host-specific to J. roemerianus, though there has been one recent report of A. lineata being detected in a DNA study of milk from cows grazing in the Italian Alps (Panelli et al 2013).…”
Section: Previous Salt Marsh Studiesmentioning
confidence: 99%